Design of switched reluctance motor as actuator in an end-effector-based wrist rehabilitation robot - Azhari, Budi; Hikmawan, Muhammad Fathul; Nugraha, Aditya Sukma; Yazid, Edwar; Pakha, Aji Nasirohman; Baskoro, Catur Hilman Adritya Haryo Bhakti; Rahmat, Rahmat; Ramadiansyah, Mohamad Luthfi (National Research and Innovation Agency, 2024)
The non-communicable diseases have become the top cause of global mortality. One of them is stroke, which also become the first cause of disability worldwide. To help rehabilitate the upper extremities function of stroke survivors, a rehabilitation aid robot is developed, also to bridge the gap between patient and medical staff numbers. An end-effector-based rehabilitation robot is one proposed device. In this case, a switched reluctance motor (SRM) can be utilized as the actuator for its simplicity, robustness, high low-speed torque, and low cost. Thus, this paper proposes a design of SRM to be used as the actuator of an end-effector-based wrist rehabilitation robot. The proposed design is made based on the required torque. To extract the outputs, calculation and simulation using finite element magnetic FEMM 4.2 are conducted. The results show that the SRM produces enough torque, according to references. Moreover, rotor tooth width reduction is not preferred, as it increases the negative torque even though it raises the saliency ratio and cuts the mass of the motor.